2021
DOI: 10.1371/journal.ppat.1009696
|View full text |Cite
|
Sign up to set email alerts
|

Novel aspects of iron homeostasis in pathogenic bloodstream form Trypanosoma brucei

Abstract: Iron is an essential regulatory signal for virulence factors in many pathogens. Mammals and bloodstream form (BSF) Trypanosoma brucei obtain iron by receptor-mediated endocytosis of transferrin bound to receptors (TfR) but the mechanisms by which T. brucei subsequently handles iron remains enigmatic. Here, we analyse the transcriptome of T. brucei cultured in iron-rich and iron-poor conditions. We show that adaptation to iron-deprivation induces upregulation of TfR, a cohort of parasite-specific genes (ESAG3, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…From the 708 genes upregulated post-irradiation in L-cluster2 and 296 genes in M-cluster1, 169 are common between the two strains ( Figure 4B , Supplementary file 4 ). This list includes repressor of differentiation kinase 2 ( RDK2 ; LmjF.31.2960) and RNA-binding protein 5 ( RBP5 ; LmjF.09.0060), both of which are involved in Trypanosoma brucei proliferation ( Gilabert Carbajo et al, 2021 ; Jones et al, 2014 ). Among the top 20 most upregulated genes in either L-cluster2 or M-cluster1 are seven genes common to both lists: serine/threonine-protein kinase NEK15 (LmjF.26.2570), adenylate-cyclase ACP2 (LmjF.10.0540), three putative surface antigen proteins (LmjF.05.1215; LmjF.12.1090 and LmjF.35.0550), one gene of unknown function (LmjF.26.2680), and a putative leucine-rich repeat (LRR) protein annotated as a pseudogene on TriTrypDB (LmjF.31.1440) ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…From the 708 genes upregulated post-irradiation in L-cluster2 and 296 genes in M-cluster1, 169 are common between the two strains ( Figure 4B , Supplementary file 4 ). This list includes repressor of differentiation kinase 2 ( RDK2 ; LmjF.31.2960) and RNA-binding protein 5 ( RBP5 ; LmjF.09.0060), both of which are involved in Trypanosoma brucei proliferation ( Gilabert Carbajo et al, 2021 ; Jones et al, 2014 ). Among the top 20 most upregulated genes in either L-cluster2 or M-cluster1 are seven genes common to both lists: serine/threonine-protein kinase NEK15 (LmjF.26.2570), adenylate-cyclase ACP2 (LmjF.10.0540), three putative surface antigen proteins (LmjF.05.1215; LmjF.12.1090 and LmjF.35.0550), one gene of unknown function (LmjF.26.2680), and a putative leucine-rich repeat (LRR) protein annotated as a pseudogene on TriTrypDB (LmjF.31.1440) ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our data reveal that VIT levels drop transcriptionally upon iron excess, and at the protein level both upon iron depletion and excess. Transcriptional and post-transcriptional control of iron uptake and storage have been examined in detail in bacteria, yeast, plants and mammalian cells (Andrews et al, 2003;Gao and Dubos, 2021;Li et al, 2008;Philpott et al, 2012;Wang and Pantopoulos, 2011), and was recently also demonstrated in the kinetoplastid parasite Trypansoma brucei (Carbajo et al, 2021). However, iron-mediated regulation has not previously been observed in the Apicomplexa.…”
Section: Discussionmentioning
confidence: 99%
“…This iron is required for a number of essential cellular processes, including heme biosynthesis (Bergmann et al, 2020;Kloehn et al, 2020), iron sulphur (Fe-S) cluster biogenesis (Aw et al, 2020), and as a cofactor in several important proteins such as catalase (Kwok et al, 2004;Odberg-Ferragut et al, 2000), prolyl hydroxylases (Florimond et al, 2019) and the deoxyribonucleotide synthesis enzyme ribonucleotide reductase. Iron acquisition and use have been studied in various pathogenic parasites such as Trichomonas (Sehgal et al, 2012) and in some detail in kinetoplastids such as Leishmania (Zaidi et al, 2017) and Trypanosoma (Carbajo et al, 2021). However, iron utilisation remains understudied in the apicomplexan parasites.…”
mentioning
confidence: 99%
“…Endocytosis assays-Endocytosis was performed as previously described [20]. Briefly, logphase trypanosome cells were washed in Hepes-buffered saline (HBS; 50 mM Hepes KOH, pH 7.5, 50 mM NaCl, 5 mM KCl, 70 mM glucose) and pre-incubated (10 6 /ml) in serum-free HMI9 with BSA (0.5 mg/ml) for 10 minutes at 37°C.…”
Section: Generation Of Gene Replacement Constructs-a Full List and De...mentioning
confidence: 99%